2009
DOI: 10.1007/s00018-009-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and antidepressants: molecular and cellular aspects

Abstract: Clinical depression is viewed as a physical and psychic disease process having a neuropathological basis, although a clear understanding of its ethiopathology is still missing. The observation that depressive symptoms are influenced by pharmacological manipulation of monoamines led to the hypothesis that depression results from reduced availability or functional deficiency of monoaminergic transmitters in some cerebral regions. However, there are limitations to current monoamine theories related to mood disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 265 publications
(227 reference statements)
0
33
0
Order By: Relevance
“…The monoamine hypothesis of depression postulates that the deficiency of neurotransmitters, such as dopamine, serotonin, and catecholamines, in the brain is responsible for the manifestations of depression (42). Assessment of the levels of serotonin and catecholamines, as well as their degradation products, in the brains of 17-mo-old NIRKO mice revealed no differences from control ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The monoamine hypothesis of depression postulates that the deficiency of neurotransmitters, such as dopamine, serotonin, and catecholamines, in the brain is responsible for the manifestations of depression (42). Assessment of the levels of serotonin and catecholamines, as well as their degradation products, in the brains of 17-mo-old NIRKO mice revealed no differences from control ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies found that depression primarily results from impaired monoaminergic neurotransmission systems [1,2]. The glutamatergic and GABAergic systems as well as several neuropeptide systems have also been the focus of pathophysiological studies on depression [1,2].…”
Section: Q2mentioning
confidence: 98%
“…The glutamatergic and GABAergic systems as well as several neuropeptide systems have also been the focus of pathophysiological studies on depression [1,2]. Inflammatory cytokines and molecular intermediates are also suggested to be involved in depression, presumably by regulating neurotransmitter metabolism, neuroendocrine function, and synaptic function [4].…”
Section: Q2mentioning
confidence: 98%
See 1 more Smart Citation
“…Performing physical exercise and environmental enrichment have also been shown to enhance hippocampal neurogenesis, potentially through increased expression of a range of mitogenic factors such as BDNF, FGF2, NGF, IGF-1 and VEGF as well as phosphorylation of cAMP-response binding protein (CREB) (Nithianantharajah, et al, 2006, Van Praag, 2008, Llorens-Martín, et al, 2009, Lafenetre, et al, 2011 and may provide an appealing noninvasive therapeutic approach for the treatment of chronic TLE (Dhanushkodi, et al, 2008, Arida, et al, 2009. Antidepressant therapy in chronic TLE is another interesting approach for increasing neurogenesis and reducing cognitive impairments, as antidepressant therapy enhances hippocampal neurogenesis probably via increases in levels of serotonin, noradrenaline, BDNF, CREB and a range of other mitogenic factors (Sahay, et al, 2007, Thomas, et al, 2008, Lanni, et al, 2009. In particular, a recent study demonstrated that repeated administration of the antidepressant agent citalopram counteracted kainic acidinduced neuronal loss and dispersion of PSA-NCAM-positive cells within the granule cell layer of the hippocampus (Jaako, et al, 2011).…”
Section: Chronic Tlementioning
confidence: 99%